ANALISIS MAKNA FIGURATIF DALAM SYAIR UMRUU AL-QAIS - Miftachul Farichah; Viyanti Malasari (Al-Lahjah, 2020)
Figurative or figure of speech is the way someone conveys something figuratively. Figurative language is a picture of the author or speaker in describing something meaning through unusual comparisons, in order to attract attention, and make something clearer. This technique is used with interesting figurative language. This indirect meaning is referred to as a figure of speech, which is a language deviation in spelling, word formation, sentence construction, or the application of a meaning. We often find this kind of phenomenon in Arabic poetry which has a double meaning or even deviates from the original meaning and then requires another meaning. This is because the form or sentence structure used by the author has a different meaning than what we imagine. Therefore, special knowledge is needed to understand these Arabic poems, one of which is understanding figurative language. By knowing the various figurative languages, Arabic learners can understand how to interpret Arabic poetry well. The analytical method used is descriptive, the form of analysis used is qualitative because the data in this analysis is in the form of lyric quotes, stanzas or lines of Arabic poetry that do not prioritize numbers. In this article, the writer tries to analyze some Arabic poetry using figurative language theory. The poetry used belongs to Umruu al-Qais.